Self-reported recent testing and diagnosis for sexually transmitted infections among regular ecstasy users in Australia, 2011–2012 - Nguyen, P.; Bruno, R.; Alati, R.; Lenton, Simon; Burns, L.; Dietze, P. (Wiley-Blackwell Publishing Ltd., 2013)
Background: Previous studies suggest that people who consume alcohol and drugs are at increased risk of sexually transmitted infections (STI). We examined the prevalence and predictors of self-reported STI testing and diagnosis among self-reported regular ecstasy users (REU). Methods: Nine hundred and fifty-five REUs from the 2011 and 2012 Ecstasy and Related Drugs Reporting System were included in the analysis. Bivariate and multivariate Poisson regression were used to identify predictors of recent STI testing, and logistic regression was used to identify predictors of recent STI diagnosis. Results: Forty-four per cent of REUs reported having a recent STI test, and 5% reported a recent diagnosis. Of the 421 REUs who reported a recent test, 10% reported a recent STI diagnosis. In multivariate analysis, REUs were more likely to report a recent STI test if they were female versus male [risk ratio (RR) = 1.56; 95% confidence interval (CI) = 1.36-1.80], aged 25–29 years versus 16–19 years (RR = 1.34; 95% CI = 1.05-1.72), or reported ≥2 casual sex partners versus no casual partners (RR = 1.48; 95% CI = 1.01–2.14). REUs reporting cannabis use in the past six months were 0.78 times less likely to report a recent STI test (95% CI = 0.66-0.94).There were no significant predictors associated with STI diagnosis. Conclusion: Encouragingly, REUs who reported having multiple casual partners in the past six months were more likely to report a recent test. However, younger REUs aged 16–19 years were least likely to test, suggesting health promotion needs to be directed to this age group. Further research is required to explain the lower testing among cannabis users.